Catalytic hydrothermal carbonization of pomelo peel for enhanced combustibility of coal/hydrochar blends and reduced CO2 emission. (15th November 2021) - Ma, Ru; Fakudze, Sandile; Shang, Qianqian; Wei, Yingyuan; Chen, Jianqiang; Liu, Chengguo; Han, Jiangang; Chu, Qiulu
Graphical abstract: Highlights: PP hydrochar modified by citric acid had superior energy yield and HHV. Synergistic effects in co-combustion of PPH220-CA and coal. Reduced CO2 emission from PPH220-CA/coal blends characterized by TG-IR. Abstract: Citric acid-modified hydrochar was prepared via the hydrothermal carbonization of pomelo peel (PP) at different temperatures (180–240 °C), and deeply explored in this paper. Based on the results, pomelo peel hydrochar prepared at 220 °C and 240 °C (PPH220-CA/PPH240-CA) were characterized by superior energy yield and HHV contents, with relatively low residual ash contents of 1.09% and 1.48%, respectively, hence were selected for co-combustion with coal. The 70%PPH220-CA/30%coal blend showed superior combustibility with an S value of 4.79 × 10 −11 . Interestingly, a synergistic effect between PPH220-CA and coal was detected during the co-combustion process, and the interaction strengthened with an increase in PPH220-CA proportion. Analysis of gas emissions via TG-IR revealed that small amounts of H2 O, CH4, CO, C = O, phenols, C-O and plentiful CO2 emissions were produced in the combustion process. Hence, the addition of PPH220-CA into fuel blends of coal can significantly reduce CO2 emissions and alleviate the greenhouse effect.